PENGARUH KUALITAS PELAYANAN PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KELURAHAN KLEAK KECAMATAN MALALAYANG KOTA MANADO - Ester, Kilapong G.; Nangoi, Grace B.; Alexander, Stanly W. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Taxpayer compliance is a law-abiding behavior. Conceptually, compliance is defined by an attempt to comply with the rules of law by a person or organization. Some factors that cause low compliance of taxpayers, among others, public dissatisfaction with public service and taxpayer knowledge of tax regulations.This study aims to determine the effect of tax service quality and tax payer knowledge on individual tax payer compliance in Kleak urban village. This research used primary data with distributing questionnaire. Questionnaires were distributed as many as 40 pieces to individual tax payer in Kleak urban village. Research sampling were taken by purposive sampling. Data were analyzed by using multiple linear regression analysis with SPSS 17 program. The results of this study indicate that the Tax Service Quality has no significant effect on individual tax payer compliance. And Tax payers Knowledge has a significant effect on individual tax payer compliance in Kleak urban village.Keywords: Tax Service Quality, Tax Payers Knowledge, Tax Compliance